KAMPANYE WORKSHOP ANTI-BULLYING KEPADA MAHASISWA PENDIDIKAN PROFESI GURU (PPG) - Khairunnisah; Normita Ika Saputri; Nursahara; Fitri Agustina; Sarmila Hasibuan; Atika Nazla Ritonga (CV. Alfa Pustaka, 2026)
Bullying in school environments is a serious problem that significantly affects students’ psychological well-being and academic achievement. Despite its prevalence, many pre-service teachers enter the profession without adequate preparation to recognise, prevent, or respond to bullying. This gap constitutes the primary problem addressed by this community service activity. This study aimed to improve the understanding, awareness, and practical skills of Professional Teacher Education (PPG) students in recognising, preventing, and handling bullying through a campaign-based workshop approach. A participatory learning method was employed, involving 19 PPG students at Universitas Muhammadiyah Tapanuli Selatan. The workshop encompassed material presentation, reflective case analysis, and the creation of anti-bullying poster products for two target audiences: teachers and students. Results indicated a meaningful increase in participants’ understanding of bullying characteristics, its multi-level impacts, and the teacher’s role as preventor, detector, and interventor. All 19 participants successfully produced anti-bullying posters meeting the five established criteria: emotional messaging (95–100%), behavioural change call to action (100%), clear reporting procedures (89–95%), accessible language (100%), and school context relevance (89–95%). These findings suggest that integrating campaign-based workshop activities into PPG curricula can substantially strengthen prospective teachers’ competence in building safe and supportive school environments